Students' Perception in Implementing Problem-Based Learning (PBL) toward Concept Understanding - Zaenudin; Asbah; Baiq Ida Astini; Isthifa Kemal (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims to analyze student perceptions of the implementation of the Problem-Based Learning (PBL) method in learning Religious Education. This study used a descriptive method with a qualitative approach, involving 80 students at Muhammadiyah Mataram University. Data were collected through a Likert scale questionnaire consisting of 50 statements, then analyzed using descriptive statistics to describe students' perceptions of the implementation of PBL. The results showed that the majority of students responded positively to this method, stating that PBL improved their understanding of religious concepts, connected religious values with daily life, and encouraged active involvement in learning. In addition, PBL is also proven to improve critical thinking skills, cooperation in group discussions, and provide a more meaningful learning experience. However, some challenges are still faced, such as limited relevant references, lack of supporting facilities, and the need for additional guidance from lecturers so that this method can be applied optimally. In addition, students emphasized the importance of real case studies in PBL to increase the relevance of learning. Therefore, support from educational institutions is needed in providing learning resources, improving learning facilities, and more structured teaching strategies. Future research is suggested to explore more flexible and effective PBL implementation strategies, as well as comparing the effectiveness of PBL with other learning methods in order to gain a more comprehensive understanding of the contribution of PBL in learning Religious Education.